Peranan Sales Promotion Dalam Upaya Meningkatkan Tingkat Hunian Wisata Dimandailing Natal - Siti Aliya Nst (Publikasi Indonesia, 2022)
The Mandailiing Natal Regency Tourism Office carries out tourism promotion by maximizing and rationalizing its promotional activities in order to attract many tourists, both domestic, domestic and foreign tourists. Advertising is one of the key factors for the success of a marketing program, so promotional activities are very important to increase the number of tourists. This study uses a descriptive qualitative approach. According to Moleong (2010:6), qualitative research aims to provide a thorough understanding of the phenomena experienced by research subjects, such as behavior, perceptions, motives, and behavior, through the explanation of words and language made. Special context that is natural and has a variety of natural ways the media in tourism marketing has an important role in conveying messages to the target. Promotion is carried out with the help of the District Tourism Office. Mandailing Natal is by utilizing the use of social media such as Instagram, Facebook, Website, and Youtube. Our social media call is Instagram. The use of social media in selling tourist attractions in Mandailing Natal, because through social media, Facebook, Instagram, Twitter can attract domestic and foreign tourists to go to Medina, because most of the earth's population lives.